Video assisted minimally invasive mitral valve surgery via right minithoracotomy: indications, techniques and results - Dinh, Nguyen Hoang; Anh, Vo Tuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.